Langkah Sukses Mahasiswa PLS dalam Mengembangkan Produk Gelang Rotan dari Bahan Daur Ulang - Yesni Nopy; Isman Isman; Sumiati Sumiati; Ruliyani Ruliyani; Anwarsani Anwarsani; Nabila Salwa; Levi Alkausar (FKIP, Universitas Palangka Raya, 2024)
Innovation in waste utilization plays a crucial role in supporting environmental sustainability and the development of the creative economy. This study explores the successful efforts of students from the Non-Formal Education (PLS) Study Program at Universitas Palangka Raya in developing rattan bracelets made from recycled materials, particularly used PVC pipes. Through a sustainability-based entrepreneurial approach, students not only reduce plastic waste but also create products with high aesthetic and economic value. The research methodology includes raw material identification, an innovative production process, and marketing strategies. The findings indicate that using PVC pipes as molds in rattan bracelet production enhances shape precision, accelerates production, and increases market appeal. Furthermore, this innovation contributes to local community empowerment and supports the Sustainable Development Goals (SDGs) in both environmental and economic aspects. Thus, the development of rattan bracelets from recycled materials not only serves as a creative solution for waste management but also opens entrepreneurial opportunities for PLS students.